Obesity impacts placental function through activation of p-IRE1a-XBP1s signaling - Shen, Wei-Bin; Wang, Bingbing; Yao, Ruofan; Goetzinger, Katherine R.; Wu, Sheng; Gao, Haijun; Yang, Peixin (Frontiers in Cell and Developmental Biology, 2023)
Maternal obesity is associated with a variety of obstetrical outcomes including stillbirth, preeclampsia, and gestational diabetes, and increases the risk of fetuses for congenital heart defects. Obesity during pregnancy represents a major contribution to metabolic dysregulation, which not only plays a key role in the pathogenesis of adverse outcome but also can potently induce endoplasmic reticulum (ER) stress. However, the mechanism associating such an obesogenic metabolic environment and adverse pregnancy outcomes has remained poorly understood. In this study, we aimed to determine whether the ER stress pathways (also named unfolded protein response (UPR)) were activated in the placenta by obesity. We collected placenta from the obese pregnancy (n=12) and non-obese pregnancy (n=12) following delivery by Caesarean-section at term. The specimens were assessed with immunocytochemistry staining and RT-QPCR. Our results revealed that in the obese placenta, p-IRE1α and XBP1s were significantly increased, CHOP and nine UPR chaperone genes were upregulated, including GRP95, PDIA6, Calnexin, p58IPK, SIL-1, EDEM, Herp, GRP58 and Calreticulin. However, Perk and BiP are not activated in the obese placenta. Our data suggest that upregulated p-IRE1α and XBP1s signaling, and UPR chaperone genes may play an important role in maternal obesity-induced placental pathology. In conclusion, this is the first report on ER stress and UPR activation in the placenta of maternal obesity. Our findings represent the first step in the understanding of one of the key ER signaling pathways, also referred to IRE1-XBP1, in placental pathophysiology affected by obesity, which may be an important mechanism accounting for the observed higher maternal and perinatal risks.